God’s spies: the Spanish Elizabethans and intelligence during the Anglo-Spanish War - Roche, Jonathan (2020)
This thesis investigates the political activities during the Anglo-Spanish War (1585-1604) of a group of English Catholic exiles, who, on account of their political alignment with the Spanish monarchy, have been called the Spanish Elizabethans. It reveals how one of this group, Hugh Owen, a Brussels-based Welsh Catholic exile, developed a sophisticated espionage network, which gathered intelligence from England. This information this network obtained was integral in the Spanish Elizabethans’ efforts to advance their political and religious ambitions: namely, the re-establishment of Catholicism in England, achieved either through a Spanish military invasion or by the accession of a Catholic candidate to the English throne upon Elizabeth’s death. The limited extent to which the Spanish Elizabethans have been studied has been a consequence of the overreliance on English-language sources, implying that the Spanish Elizabethans were only concerned with, and involved in, English politics. This thesis, though, adopts a broader analytical approach. Drawing on material from Spain and Italy in addition to English sources, it argues that the Spanish Elizabethans were active participants in political debates across Europe and shows how the English intelligence provided by the Spanish Elizabethans shaped these discussions. The Spanish authorities in Madrid and Brussels, as well as the Papacy in Rome, had to be persuaded that committing military and financial resources to the cause of English Catholicism was the best use of these limited resources. Intelligence, gathered from England by Owen’s espionage network, was crucial in this endeavour, forming an integral part of a multi-faceted campaign which also included printed texts, military proposals, and persistent lobbying. Moreover, through an investigation of the intelligence reports sent by Hugh Owen to Spain – the avisos de Inglaterra – this thesis explores the direct impact of Spanish Elizabethan intelligence on the Anglo-Spanish War, revealing previously unknown details about the conflict which, in English-language historiography, is usually examined from an Elizabethan perspective alone. By examining how the Spanish Elizabethans developed an extensive and sophisticated espionage apparatus to obtain intelligence from England, and exploring how this intelligence was used and the impact that it had on political and military discussions in Madrid, Brussels, and Rome, this thesis highlights the variety and vitality of Reformation politics at the end of the sixteenth century.